Exploring the Influence of Digitally Mediated Communication on Language and Traditional Speech Communities: a Descriptive Sociolinguistic Approach - DATONDJI, COCOU ANDRÉ (My University, 2018)
The advent and fast development of digital technologies in human communication has greatly influenced the language used for both professional purposes and leisure activities. This article investigated the impact of the subsequent growing number of virtual communities on language and on traditional face to face interaction speech communities. This article concluded that the language used in digitally mediated communication is one of its kind.
Keywords: social media; mediated communication; linguistic communities; lexico-syntactic peculiarities.